India’s medical tourism analysis and forecasting - Ahire, Manoj Popatrao (2019)
The paper deals with India Medical tourism analysis and forecasting, applying an assortment of time series forecasting models, for monthly data spreading over 2014 to 2018. Medical tourism worldwide and in India is on rise. Figures of medical tourist arrivals in India for 2014, 2015 and 2016 suggest of a significant growth. A number of measures have been taken by the Government to attract medical tourists to the country. This study was undertaken to analyse the growth trends in medical tourism in India over a period of last five years and also to project the medical tourist arrivals over the next couple of years using the sophisticated ARIMA method of trend projection. The paper discusses these trends including their calculations. The projections show a great potential for the country to earn valuable foreign exchange through medical tourism. India has a huge cost and expertise advantage which if leveraged through proper publicity can make it one of the leading medical tourist destinations in the days to come. The Government should step-up its efforts in this direction with aggressive publicity policies.